(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This Research aimed to measure the level of Stress among sample of teachers of the first cycle of the basic education in Lattakia city, and determine the most common factor of personality among them, and investigates the relationship between the level of Stress and the Big Five Factor of personality, as well as an investigating the possibility of predicting the level of Stress through the Big Five Factor. To achieve the research objectives, the descriptive method was used, and the tow search tools were: The Stress scale for teachers of AL-Asmy, and the big five factors of personality scale of Costa and McCare with its translated version into Arabic. The research sample included (360) male and female teachers of the first cycle of basic education in Lattakia city. The results showed that the level of Stress among teachers of the research sample is high, and the low levels of: (Extroversion, Openness to experience, Agreeableness) among teachers leads to a high level of Stress, and the high levels of: (Neuroticism and Conscientiousness) lead to a high of Stress, and the Stress of teachers can be predicted through factors: (Extroversion, Openness to experience, Agreeableness, Neuroticism Conscientiousness(, in addition , the most common personality factor among teachers was Conscientiousness. Based on the research results, some suggestions were made, including: preparing and implementing counseling and remedial programs for teachers in the service phase; those who suffer from Stress, and training teachers in the pre-service stage on the application of strategies to alleviate Stress.